Preparation method of multi-system composite shell for directional and single-crystal blades
By adopting the preparation method of multi-material system composite shell, the problem that existing ceramic shells are difficult to take into account both wet strength, thermal deformation performance and concession under high temperature environments is solved, and the comprehensive performance of ceramic shells is improved, reducing the Defects and costs during casting.
Patent Information
- Application Number
- CN202411573124.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing directional and single-crystal blade ceramic shells are difficult to take into account the wet strength, thermal deformation performance and concession in high temperature environments, resulting in cracking, steel leakage and recrystallization problems during the casting process, making it difficult to adapt to the improvement of blade performance requirements. .
The preparation method of multi-material system composite shell is adopted. Through the design of multi-layer ceramic shell, ceramic powder and sand materials of different particle sizes and components are used, combined with alkaline silicon sol and quick-drying silicon sol and other binders to prepare the surface. The slurry of the layer, transition layer and back layer is formed by a specific coating and drying step.
It significantly improves the wet strength and high temperature strength of the ceramic shell, and at the same time improves the concession and collapse properties, reduces the steel leakage problem caused by cracking of the shell, avoids recrystallization and crack defects, and improves the quality stability of the casting process. process yield of properties and blade metallurgical quality.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of manufacturing directional and single crystal blade ceramic shells for investment casting, and in particular to a method for preparing a multi-system composite shell for directional and single crystal blades. Background Art
[0002] Directed blades and single crystal blades are one of the most critical parts in aircraft engine manufacturing. Under working conditions, they need to bear loads repeatedly in a high temperature environment, and the required performance requirements are very high, so higher requirements are also placed on the casting process. The precision casting of directional and single crystal blades requires the ceramic shell to have high wet strength and high temperature strength, low thermal deformation performance and good yieldability. The above performance is a necessary condition for the manufacture of directional and single crystal blades, but the improvement of strength and yieldability is a contradiction and a difficulty in improving the comprehensive performance of the shell.
[0003] With the development of engine technology, the alloy types, blade structures, performance and size requirements of directional and single crystal blades, especially single crystal blades, have also changed significantly, and the difficulty of casting has gradually increased. One of the key difficulties is reflected in the shell technology. At present, directional single crystal blades mostly use a single material system for shell making, and lack the modification of raw materials and shell slurry. It cannot take into account the improvement of various performances. There are many restrictions on the improvement of comprehensive performance, and it is difficult to adapt to the development needs of blades. Therefore, the research and development of such technical methods is very necessary. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a method for preparing a multi-system composite shell for oriented and single crystal blades; the specific technical scheme is as follows:
[0005] A method for preparing a multi-system composite shell for directional and single crystal blades, wherein the ceramic shell adopts a multi-layer ceramic shell for investment casting, and the mold tree is degreased and dried before the surface slurry is applied, and then fused corundum sand or zircon sand is spread, and after drying, the transition layer and the back layer are applied, sanded and dried in the above manner respectively; finally, the shell is dewaxed and calcined to complete the production;
[0006] The materials required for preparing the ceramic shell include surface layer refractory powder, surface layer refractory sand, transition layer refractory powder, transition layer refractory sand, back layer refractory powder, back layer refractory sand, binder, penetrant, defoamer;
[0007] The surface layer powder material is 325 mesh fused corundum powder or 325 mesh zircon powder;
[0008] The surface refractory sand material is fused corundum sand with a particle size of 80-100 mesh;
[0009] The transition layer powder is 325 mesh fused corundum powder or 325 mesh fused mullite powder, wherein the composition of fused mullite is Al 2 O 3 Content 91%~98%, SiO 2 The content is 3% to 8%;
[0010] The transition layer refractory sand material is fused corundum sand with a particle size of 36-60 mesh;
[0011] The back layer refractory powder is selected from 325 mesh fused mullite powder or modified fused quartz powder or zircon powder; wherein the fused mullite component is Al 2 O 3 Content 91%~98%, SiO 2 The content is 3% to 8%; the modified fused quartz powder components are 90% to 95% fused quartz powder, 3% to 8% graphite powder, and 1% to 3% organic fiber; the zircon powder component is ZrO 2 Content ≥ 65%, SiO 2 Content ≥32%;
[0012] The back layer refractory sand material is fused corundum sand or fused mullite sand, with a particle size of 16-46 mesh;
[0013] The binder is alkaline silica sol or quick-drying silica sol; wherein SiO 2 The content is 29% to 31%. When using alkaline silica sol, a reinforcing agent needs to be added to form a mixed solution of alkaline silica sol and reinforcing agent; when using quick-drying silica sol, no reinforcing agent is added;
[0014] The penetrant is fatty alcohol polyoxyethylene ether;
[0015] The defoaming agent is n-octanol.
[0016] A method for preparing a multi-system composite shell for oriented and single crystal blades, wherein the method for preparing a ceramic shell by using materials for making the ceramic shell comprises the following steps:
[0017] Step 1: prepare surface slurry;
[0018] Mix fused corundum powder or zircon powder with silica sol, penetrant and defoamer, the ratio of powder to binder is (3.2-4.2):1, the amount of penetrant and defoamer added is 1‰-5‰ of the weight of the binder; the viscosity of the prepared slurry is 25s-40s, which can be tested by 6# viscometer;
[0019] Step 2: preparing transition layer slurry;
[0020] Mix fused corundum powder or fused mullite powder, alkaline silica sol or quick-drying silica sol, penetrant and defoamer, the ratio of powder to binder is (1.5-3.0):1, the amount of penetrant and defoamer added is 1‰-5‰ of the weight of the binder; the viscosity of the prepared slurry is 8s-15s, which can be detected by 6# viscometer;
[0021] Step 3: preparing backing layer slurry;
[0022] Preparation of backing slurry made of fused mullite powder: Mix fused mullite powder, alkaline silica sol and reinforcing agent mixture or quick-drying silica sol, penetrant and defoamer, the ratio of powder to binder (1.5-3.5): 1, the amount of penetrant and defoamer added is 1‰-5‰ of the weight of the binder; the viscosity of the prepared slurry is 8s-20s and can be tested by 6# viscometer;
[0023] The preparation of the backing slurry made of modified fused quartz powder: 90-95 parts of fused quartz powder, 3-8 parts of graphite powder, and 1-3 parts of organic fiber are used to form a mixed powder, and then mixed with alkaline silica sol and reinforcing agent mixed liquid or quick-drying silica sol and penetrant. The ratio of modified powder to silica sol is (1.0-2.8): 1, and the amount of penetrant and defoamer added is 1‰-5‰ of the weight of the binder; the viscosity of the prepared slurry is 6s-16s, which can be detected by a 10# viscometer;
[0024] Preparation of backing slurry made of zircon powder: Mix zircon powder, alkaline silica sol, reinforcing agent mixture and penetrant, the ratio of powder to silica sol mixture is (2.0-3.5):1, the amount of penetrant and defoamer added is 1‰-5‰ of the weight of the binder; the slurry viscosity is 8s-17s, tested by 6# viscometer;
[0025] Step 4: prepare sealing layer slurry;
[0026] The ratio of fused corundum powder or fused mullite powder to alkaline silica sol and reinforcing agent mixture or quick-drying silica sol is (2-2.7):1, and the amount of penetrant and defoamer added is 1‰-5‰ of the weight of the binder; the viscosity of the prepared slurry is 10s-23s, which can be detected by 6# viscometer;
[0027] Step 5: After the module soaks the surface slurry and controls the material, it is coated with 80-100 mesh fused corundum sand and then dried;
[0028] Step 6: Immerse the module in the transition layer fused mullite powder / fused corundum powder slurry and control the material, apply 36-60 mesh fused corundum sand, and then dry it;
[0029] Step 7: Immerse the module in the back layer modified fused quartz powder / zircon powder slurry and control the material, spread 16-46 mesh fused corundum sand / fused mullite sand, and then dry it;
[0030] Step 8: Immerse the module in the fused mullite powder slurry of the transition layer and control the material, or mix it with the backing layer, apply 16-46 mesh fused corundum sand / fused mullite sand, and then dry it.
[0031] Step 9: Apply the sealing slurry layer and dry it. The viscosity of the sealing slurry layer is 10s to 23s;
[0032] Step 10: Dewaxing the coated shell;
[0033] Step 11: sintering the coated shell.
[0034] The method for preparing a multi-system composite shell for directional and single crystal blades, the preferred embodiment of which is that the reinforcing agent in the alkaline silica sol is styrene-butadiene latex, the solid content is 42% to 48%, and the pH value is 10 to 10.5;
[0035] The mixture of alkaline silica sol and reinforcing agent comprises 90% to 95% silica sol and 5% to 10% reinforcing agent.
[0036] The preferred embodiment of the method for preparing a multi-system composite shell for directional and single crystal blades is that the multi-system mainly refers to refractory powder.
[0037] The method for preparing a multi-system composite shell for a directional and single crystal blade, the preferred embodiment of which is that the refractory powders used are as follows: the surface layer slurry is represented by MG; the transition layer slurry is represented by GG (M), wherein GG represents corundum powder slurry and GM represents fused mullite slurry; the back layer fused mullite powder slurry, modified fused quartz powder slurry, and zircon powder slurry are represented by BM, BR, and BG, respectively;
[0038] The number of coating layers is required to be 4 to 7 layers according to the blade structure and size;
[0039] The coating process for 4-7 layer shell is as follows:
[0040] 4 layers: MG-GG(M)-BR-BM
[0041] 5-layer: MG-GG(M)-BR-BG-BM or MG-GG(M)-BR-BM-BM or MG-GG(M)-BG-BG-BM
[0042] 6-layer: MG-GG(M)-BR-BG-BM-BM or MG-GG(M)-BR-BR-BM-BM or MG-GG(M)-BG-BG-BM-BM
[0043] 7th layer: MG-GG(M)-BR-BM-BR-BM-BM or MG-GG(M)-BG-BM-BG-BM-BM or MG-GG(M)-BR-BG-BM-BM-BM.
[0044] Compared with the prior art, the present invention has the following beneficial technical effects:
[0045] The present invention adopts a multi-material system composite and modified to prepare the shell, which combines the characteristics of high strength, high thermal stability, and easy collapse. The wet strength of the ceramic shell can be improved, and the yield of the shell can be significantly improved while ensuring the high-temperature strength. This method can improve the comprehensive performance of the shell while ensuring that the single-crystal blade shell has a thin thickness. It can prevent the shell from cracking due to dewaxing in the shell making stage, ensure that the shell has excellent high-temperature strength in the high-temperature pouring stage, make the shell have appropriate yield in the solidification stage, have good collapsibility in the shelling stage, improve the quality stability of the casting process, reduce the problem of steel leakage caused by shell cracking, avoid defects such as orientation and single-crystal blade recrystallization and cracks caused by poor shell yield, and improve the process yield of blade metallurgical quality.
[0046] Compared with the existing technology, this method can increase the wet strength of the shell by 50%-70%, and reduce the residual strength of the shell by 30%-40% while ensuring the high-temperature strength. It avoids product scrapping due to steel leakage and problems such as recrystallization and blade cracks in the solidification process, greatly reduces the cost of scrap caused by defects, and improves the quality and reliability of the blade. DETAILED DESCRIPTION
[0047] Embodiment 1:
[0048] A method for preparing a multi-system composite shell for oriented and single crystal blades, the specific steps are as follows:
[0049] Step 1: prepare surface slurry;
[0050] Mix 3.5 parts of fused corundum powder and 1 part of silica sol to prepare a surface slurry with a viscosity of (27±2)s;
[0051] Step 2: preparing transition layer slurry;
[0052] 2.5 parts of fused mullite powder and 1 part of a mixture of silica sol and reinforcing agent were mixed and stirred to prepare a transition layer slurry with a slurry viscosity of (12±2)s;
[0053] Step 3: preparing backing layer slurry;
[0054] 94 parts of fused silica powder, 5 parts of graphite powder and 1 part of organic fiber were mixed into a powder. Then 2.0 parts of the mixed powder was mixed and stirred with 1 part of silica sol to prepare a backing layer slurry with a slurry viscosity of (10±2)s;
[0055] Step 4: prepare sealing layer slurry;
[0056] 2.5 parts of fused mullite powder and 1 part of a mixture of silica sol and a reinforcing agent are mixed and stirred to prepare a sealing slurry with a viscosity of (15±1)s;
[0057] Step 5: After the module is soaked in the surface slurry and the material is controlled, 100 mesh fused corundum sand is applied and then dried;
[0058] Step 6: Immerse the module in the transition layer fused mullite powder slurry and control the material, apply 60 mesh fused corundum sand, and then dry it;
[0059] Step 7: Immerse the module in the back layer modified fused quartz powder slurry and control the material, apply 24 mesh fused corundum sand, and then dry it;
[0060] Step 8: Immerse the module in the transition layer or the fused mullite powder slurry that can be mixed with the back layer and control the material, apply 24 mesh fused corundum sand, and then dry it;
[0061] Step nine: Apply a sealing slurry layer and dry it; the viscosity of the sealing slurry layer is 15s;
[0062] Step 10: Dewaxing the coated shell;
[0063] Step 11: sintering the coated shell.
[0064] Embodiment 2:
[0065] A method for preparing a multi-system composite shell for oriented and single crystal blades, the specific steps are as follows:
[0066] Step 1: prepare surface slurry;
[0067] Mix 3.6 parts of fused corundum powder and 1 part of silica sol to prepare a surface slurry with a viscosity of (28±2)s;
[0068] Step 2: Prepare transition layer fused corundum powder slurry;
[0069] 2.7 parts of fused corundum powder and 1 part of silica sol were mixed and stirred to prepare a transition layer slurry with a slurry viscosity of (11±2)s;
[0070] Step 3: preparing back layer fused quartz powder slurry;
[0071] 91 parts of fused silica powder, 6 parts of graphite powder, and 3 parts of organic fiber were mixed into a powder. Then 2.3 parts of the mixed powder was mixed and stirred with 1 part of silica sol to prepare a backing layer slurry with a slurry viscosity of (14±2)s;
[0072] Step 4: preparing back layer zirconium powder slurry;
[0073] First, the silica sol and the reinforcing agent are prepared into a mixed liquid in a weight ratio of 9:1; then 2.0 parts of zircon powder and 1 part of the mixed liquid are mixed and stirred to prepare a slurry for the back layer, and the slurry viscosity is (8±2)s;
[0074] Step 5: preparing back layer fused mullite powder slurry;
[0075] 2.3 parts of fused mullite powder and 1 part of silica sol are mixed and stirred to prepare a transition layer slurry with a slurry viscosity of (9±2)s; the slurry can be used as a sealing layer slurry;
[0076] Step 6: After the module is soaked in the surface slurry and the material is controlled, 80 mesh fused corundum sand is applied and then dried;
[0077] Step 7: Immerse the module in the transition layer fused corundum powder slurry and control the material, apply 60 mesh fused corundum sand, and then dry it;
[0078] Step 8: Immerse the module in the back layer modified fused quartz powder slurry and control the material, apply 46 mesh fused corundum sand, and then dry it;
[0079] Step 9: Immerse the module in the back layer zircon powder slurry and control the material, apply 46 mesh fused corundum sand, and then dry it;
[0080] Step 10: Immerse the mold into the back layer fused mullite powder slurry and control the material, apply 24 mesh fused corundum sand, and then dry; repeat this action 2 times to apply 7 layers of shell;
[0081] Step 11: Apply a sealing layer and dry it;
[0082] Step 12: Dewaxing the coated shell;
[0083] Step 13: sintering the coated shell.
[0084] Matters not covered by the present invention are known technologies.
[0085] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a multi-system composite shell for directional and single crystal blades, characterized in that: The ceramic shell adopts the multi-layer ceramic shell method for investment casting. After the mold tree is degreased and dried, the surface slurry is applied, and then fused corundum sand or zircon sand is spread. After drying, the transition layer and the back layer are applied, sanded and dried in the above manner respectively; finally, the shell is made after dewaxing and roasting; The materials required for preparing the ceramic shell include surface layer refractory powder, surface layer refractory sand, transition layer refractory powder, transition layer refractory sand, back layer refractory powder, back layer refractory sand, binder, penetrant, defoamer; The surface layer powder material is 325 mesh fused corundum powder or 325 mesh zircon powder; The surface refractory sand material is fused corundum sand with a particle size of 80-100 mesh; The transition layer powder is selected from 325 mesh fused corundum powder or 325 mesh fused mullite powder, wherein the composition of the fused mullite is 91% to 98% Al2O3 and 3% to 8% SiO2; The transition layer refractory sand material is fused corundum sand with a particle size of 36-60 mesh; The back layer refractory powder is selected from 325 mesh fused mullite powder or modified fused quartz powder or zircon powder; wherein the fused mullite composition is 91% to 98% Al2O3 content and 3% to 8% SiO2 content; the modified fused quartz powder composition is 90% to 95% fused quartz powder, 3% to 8% graphite powder, and 1% to 3% organic fiber; the zircon powder composition is ≥65% ZrO2 content and ≥32% SiO2 content; The back layer refractory sand material is fused corundum sand or fused mullite sand, with a particle size of 16-46 mesh; The binder is alkaline silica sol or quick-drying silica sol; wherein the SiO2 content in the alkaline silica sol is 29% to 31%, and when the alkaline silica sol is used, a reinforcing agent needs to be added to form a mixed liquid of the alkaline silica sol and the reinforcing agent; when the quick-drying silica sol is used, no reinforcing agent is added; The penetrant is fatty alcohol polyoxyethylene ether; The defoaming agent is n-octanol.
2. The method for preparing a multi-system composite shell for directional and single crystal blades according to claim 1, characterized in that: The method for preparing a ceramic shell by using a material for making a ceramic shell comprises the following steps: Step 1: prepare surface slurry; Mix fused corundum powder or zircon powder with silica sol, penetrant and defoamer, the ratio of powder to binder is (3.2-4.2):1, the amount of penetrant and defoamer added is 1‰-5‰ of the weight of the binder; the viscosity of the prepared slurry is 25s-40s, which can be tested by 6# viscometer; Step 2: preparing transition layer slurry; Mix fused corundum powder or fused mullite powder, alkaline silica sol or quick-drying silica sol, penetrant and defoamer, the ratio of powder to binder is (1.5-3.0):1, the amount of penetrant and defoamer added is 1‰-5‰ of the weight of the binder; the viscosity of the prepared slurry is 8s-15s, which can be detected by 6# viscometer; Step 3: preparing backing layer slurry; Preparation of backing slurry made of fused mullite powder: Mix fused mullite powder, alkaline silica sol and reinforcing agent mixture or quick-drying silica sol, penetrant and defoamer, the ratio of powder to binder (1.5-3.5): 1, the amount of penetrant and defoamer added is 1‰-5‰ of the weight of the binder; the viscosity of the prepared slurry is 8s-20s and can be tested by 6# viscometer; The preparation of the backing slurry made of modified fused quartz powder: 90-95 parts of fused quartz powder, 3-8 parts of graphite powder, and 1-3 parts of organic fiber are used to form a mixed powder, and then mixed with alkaline silica sol and reinforcing agent mixed liquid or quick-drying silica sol and penetrant. The ratio of modified powder to silica sol is (1.0-2.8): 1, and the amount of penetrant and defoamer added is 1‰-5‰ of the weight of the binder; the viscosity of the prepared slurry is 6s-16s, which can be detected by a 10# viscometer; Preparation of backing slurry made of zircon powder: Mix zircon powder, alkaline silica sol, reinforcing agent mixture and penetrant, the ratio of powder to silica sol mixture is (2.0-3.5):1, the amount of penetrant and defoamer added is 1‰-5‰ of the weight of the binder; the slurry viscosity is 8s-17s, tested by 6# viscometer; Step 4: prepare sealing layer slurry; The ratio of fused corundum powder or fused mullite powder to alkaline silica sol and reinforcing agent mixture or quick-drying silica sol is (2-2.7):1, and the amount of penetrant and defoamer added is 1‰-5‰ of the weight of the binder; the viscosity of the prepared slurry is 10s-23s, which can be detected by 6# viscometer; Step 5: After the module soaks the surface slurry and controls the material, it is coated with 80-100 mesh fused corundum sand and then dried; Step 6: Immerse the module in the transition layer fused mullite powder / fused corundum powder slurry and control the material, apply 36-60 mesh fused corundum sand, and then dry it; Step 7: Immerse the module in the back layer modified fused quartz powder / zircon powder slurry and control the material, spread 16-46 mesh fused corundum sand / fused mullite sand, and then dry it; Step 8: Immerse the module in the fused mullite powder slurry of the transition layer and control the material, or mix it with the backing layer, apply 16-46 mesh fused corundum sand / fused mullite sand, and then dry it. Step 9: Apply the sealing slurry layer and dry it. The viscosity of the sealing slurry layer is 10s to 23s; Step 10: Dewaxing the coated shell; Step 11: sintering the coated shell.
3. The method for preparing a multi-system composite shell for directional and single crystal blades according to claim 1, characterized in that: The reinforcing agent in the alkaline silica sol is styrene-butadiene latex, with a solid content of 42% to 48% and a pH value of 10 to 10.5; The mixture of alkaline silica sol and reinforcing agent comprises 90% to 95% silica sol and 5% to 10% reinforcing agent.
4. The method for preparing a multi-system composite shell for directional and single crystal blades according to claim 1, characterized in that: The multi-system mainly refers to refractory powder.
5. The method for preparing a multi-system composite shell for directional and single crystal blades according to claim 4, characterized in that: The refractory powders used are as follows: the surface layer slurry is represented by MG; the transition layer slurry is represented by GG(M), where GG represents corundum powder slurry and GM represents fused mullite slurry; the back layer fused mullite powder slurry, modified fused quartz powder slurry, and zircon powder slurry are represented by BM, BR, and BG respectively; The number of coating layers is required to be 4 to 7 layers according to the blade structure and size; The coating process for 4-7 layer shell is as follows: 4 layers: MG-GG(M)-BR-BM 5-layer: MG-GG(M)-BR-BG-BM or MG-GG(M)-BR-BM-BM or MG-GG(M)-BG-BG-BM 6-layer: MG-GG(M)-BR-BG-BM-BM or MG-GG(M)-BR-BR-BM-BM or MG-GG(M)-BG-BG-BM-BM 7th layer: MG-GG(M)-BR-BM-BR-BM-BM or MG-GG(M)-BG-BM-BG-BM-BM or MG-GG(M)-BR-BG-BM-BM-BM.
Citation Information
Patent Citations
High-performance ceramic mold shell for directional solidification, and production technology thereof
CN104772429A
Composite modified ceramic shell and preparation method thereof
CN109128037A
Ceramic shell material for precision casting of superalloy castings and preparation method of ceramic shell material
CN112439874A
High-permeability directional / single crystal blade ceramic shell and preparation method thereof
CN115608928A